The semantics of silence in biblical Hebrew - Noll, Sonja (Studies in Semitic languages and linguistics, 2020)
"In The Semantics of Silence in Biblical Hebrew, Sonja Noll explores the many words in biblical Hebrew that refer to being silent, investigating how they are used in biblical texts, Dead Sea Scrolls, and Ben Sira. She also examines the tradition of interpretation for these words in the early versions (Septuagint, Vulgate, Targum, Peshitta), modern translations, and standard dictionaries, revealing that meanings are not always straightforward and that additional work is needed in biblical semantics and lexicography. The traditional approach to comparative Semitics, with its over-simplistic assumption of semantic equivalence in cognates, is also challenged. The surprising conclusion of the work is that there is no single concept of silence in the biblical world; rather, it spans multiple semantic fields"--